Pengaruh Keaktifan Berorganisasi Terhadap Prestasi Akademik Mahasiswa Reguler Angkatan 2018 STIM Lasharan Jaya Makassar - Arfiany Arfiany; Jamilah Jamilah (STIM LASHARAN JAYA MAKASSAR, 2018)
This study aims to determine the Influence of Organizational Activity on Academic Achievement of Regular Students Class of 2018 STIM Lasharan Jaya Makassar. So the objectives to be achieved in this research are: 1) To find out whether student activity in organizations affects the achievement of regular students of the 2018 STIM Lasharan Jaya Makassar class. 2) To find out what factors cause students who follow the organization tend to have low academic achievement. The types of research data used in this research are quantitative data types, and through data collection techniques, namely; observations, questionnaires, and interviews. The sampling method used in this research is non-probability sampling - purposive sampling to obtain 55 samples or respondents. The data analysis techniques used in this research are validity test and reliability test. And the data analysis method uses simple linear regression analysis Y' = a + bX The statistical analysis used in this study is simple regression analysis using the SPSS version 22 program. The findings of this study indicate that the variable of Organizational Activeness simultaneously has a significant effect on the academic achievement of the 2018 STIM Lasharan Jaya Makassar regular students. This has been proven by the results of the t-test of the independent variable partially affecting the dependent variable if the level of significance is below 0.05. The results of the study indicate that there is an influence of organizational activity on student academic achievement